2016
DOI: 10.3847/0004-637x/825/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Shock Connectivity in the 2010 August and 2012 July Solar Energetic Particle Events Inferred From Observations and Enlil Modeling

Abstract: During periods of increased solar activity, coronal mass ejections (CMEs) can occur in close succession and proximity to one another. This can lead to the interaction and merger of CME ejecta as they propagate in the heliosphere. The particles accelerated in these shocks can result in complex solar energetic particle (SEP) events, as observing spacecraft form both remote and local shock connections. It can be challenging to understand these complex SEP events from in situ profiles alone. Multipoint observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 52 publications
0
47
0
Order By: Relevance
“…Pre-event particle intensities were low at all three locations, and a week had elapsed since the previous SEP event observed on 2010 August 7 by STEREO-B and near-Earth spacecraft, but not by STEREO-A (Richardson et al 2014). The IP shock associated with this prior SEP event was observed in situ by STEREO-B and near-Earth spacecraft on 2010 August 11 (Bain et al 2016), indicating that transient solar wind structures were absent at the time of the onset of the 2010 August 14 SEP event (see Figure1 in Bain et al 2016).…”
Section: The Sep Event On 2010 August 14: Contextmentioning
confidence: 91%
See 3 more Smart Citations
“…Pre-event particle intensities were low at all three locations, and a week had elapsed since the previous SEP event observed on 2010 August 7 by STEREO-B and near-Earth spacecraft, but not by STEREO-A (Richardson et al 2014). The IP shock associated with this prior SEP event was observed in situ by STEREO-B and near-Earth spacecraft on 2010 August 11 (Bain et al 2016), indicating that transient solar wind structures were absent at the time of the onset of the 2010 August 14 SEP event (see Figure1 in Bain et al 2016).…”
Section: The Sep Event On 2010 August 14: Contextmentioning
confidence: 91%
“…The IP shock associated with the CME on 2010 August 14 was observed in situ by STEREO-A at ∼17:50 UT on 2010 August 17 (day of year 229) followed by a magnetic cloud (see Bain et al 2016 and references therein; this is shock S5 in their Figure1). Bain et al (2016) did not identify a corresponding shock at Earth, but a candidate weak shock-like feature passed L1 (specifically, the Wind spacecraft) at ∼23:25UT on 2010 August 17 (day 229).…”
Section: The Sep Event On 2010 August 14: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its moderate strength, this proton event received a lot of attention as it was the first proton event affecting Earth that was recorded since December 2006 and the only one observed during the year 2010, according to NOAA. 1 Bain et al (2016) performed a detailed study on the SEP events that were observed in August 2010 and combined observations with various modeling techniques to understand the shock connectivity for and interaction between these events.…”
Section: Coronagraphmentioning
confidence: 99%